Докембрий и проблемы формирования земной коры - Сидоренко А. В.; Теняков В. А.; Сидоренко Св. А.; Созинов Н. А.; Розен О. М.; Борщевский Ю. А.; Ганеев И. Г.; Гиммельфарб Г. Б.; Горбачев О. В.; Корякин А. С.; Тимофеев П. П. (Москва, Наука, 1978)
Доп. тит. лист на английском языке